IKLIM KOMUNIKASI PT KAI (PERSERO) DAOP 8 SURABAYA DALAM MENINGKATKAN PRODUKTIVITAS KARYAWAN MELALUI KEGIATAN EMPLOYEE RELATIONS - Ita Nurlita; Rini Ganefwati; Awanis Ade Tasya Winarno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
In every company basically requires good communication in an effort to achieve the goals to be achieved. Thus, to support smooth communication within the company, it is also necessary to be supported by a good organizational communication climate. The organizational communication climate also occurs at PT KAI (Persero) Daop 8 Surabaya. Organizational communication climate, with its existence, is so important in influencing the way of life of its members so that it has an influence on the productivity of its performance. This study aims to analyze the communication climate at PT KAI (Persero) Daop 8 Surabaya in increasing employee productivity through employee relations activities and to analyze the obstacles that occur in the communication climate. The research method used by researchers is a descriptive quantitative research method, by analyzing the communication climate at PT KAI (Persero) Daop 8 Surabaya. Based on the results of a crosstab analysis of 6 indicators of organizational communication climate according to Faules and Pace including, trust, shared decisions, honesty, listening in upward communication, openness in downward communication, and attention to high-performance goals, the average results are obtained for each indicator that the organizational communication climate on PT KAI Daop 8 Surabaya employee productivity is fairly good, namely 4.02 which indicates that the communication climate at PT. KAI (Persero) Daop 8 Surabaya is running quite well. Keywords : Communication Climate, Employee Relations, Productivity